Mechanical properties and cracking behavior of rebar reinforced UHPC (R-UHPC) under uniaxial tension: Evaluation and design - Xianzhi Luo; Sumei Zhang; Yuchen Zhang; Yuexin Jiang (Case Studies in Construction Materials)
Incorporating steel rebar into ultra-high performance concrete (UHPC) to form rebar-reinforced UHPC (R-UHPC) represents one of the primary applications of this high-performance material. However, the issues of deformability degradation and high material cost in R-UHPC still hinder its broader application. In order to achieve the target deformability and effectively utilize steel fibers, this study systematically investigates the mechanical properties and cracking behavior of 60 UHPC specimens featuring diverse fiber dosages (0.5 %, 1.0 %, 2.0 %, and 3.0 %) and reinforcement ratios (0 %, 1.7 %, 3.0 %, 4.7 %, and 6.8 %) under axial tensile loading. The research findings reveal that the tensile deformability of R-UHPC depends on the combination of reinforcement ratio and fiber dosage, rather than a single parameter. The additional load-bearing capacity provided by strain-hardening of rebar cannot cover the load transfer from UHPC to rebar during the tensile cracking process, causing deformability degradation of R-UHPC. The tensile strength of UHPC in R-UHPC is lower than that of UHPC without rebar at the same fiber dosage, which needs to be considered when calculating the tensile load-bearing capacity. The crack resistance of R-UHPC with fiber dosage as low as 0.5 % is sufficient to meet the requirements for maximum crack width of reinforced members in all exposure classes specified in Eurocode 2 and fib Model Code 2010, which tend to overestimate the maximum crack width of low fiber dosage R-UHPC with low fiber dosage. Increasing the fiber dosage from 0.5 % onwards improves crack resistance, but the effect of reinforcement ratio variation is limited. The method for calculating the minimum reinforcement ratio to avoid tensile deformability degradation, and the method for calculating the tensile load-bearing capacity of R-UHPC are proposed and validated.